Biomimetic Mineralization of Protein Nanogels for Enzyme Protection. Issue 72 (6th December 2019) - Yu, Qianyu; Ma, Xiaoteng; Liu, Yingze; Zhao, Hanying
Abstract: Protein nanogels have found a wide variety of applications, ranging from biocatalysis to drug/protein delivery. However, in practical applications, proteins in nanogels may suffer from enzymic hydrolysis and denaturation. Inspired by the structure and functionalities of the fowl eggshells, biomimetic mineralization of protein nanogels was studied in this research. Protein nanogels with embedded porcine pancreas lipase (PPL) in the cross‐linked nanostructures were synthesized through the thiol–disulfide reaction between thiol‐functionalized PPL and poly( N ‐isopropylacrylamide) with pendant pyridyl disulfide groups. The nanogels were further reacted with reduced bovine serum albumin (BSA) and BSA molecules were coated on the nanogels. Mineralization of BSA leads to the synthesis of biomineralized shells on the nanogels. With the growth of CaCO3 on the shells, the nanogels aggregate into suprastructures. Thermogravimetric analysis, XRD, dynamic light scattering, and TEM were employed to study the mechanism of the biomineralization process and analyze the structures of the mineralized nanogels. The biomineralized shells can effectively protect the PPL molecules from hydrolysis by trypsin; meanwhile, the nanosized channels on the mineralized shells allow the transport of small‐molecule substrates across the shells. Bioactivity measurements indicate that PPL in the nanogels maintains more than 80 % bioactivity after biomineralization. Abstract : Protective shell : Mineralization of protein nanogels with embedded porcine pancreas lipase and bovine serum albumin layers leads to the synthesis of mineralized shells, which can effectively protect the enzyme molecules in the nanostructures and facilitate the exchange of the substrates (see figure).